2013
DOI: 10.1371/journal.pone.0067300
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Salmonella typhimurium Infection Leads to miR-29a Induced Caveolin 2 Regulation

Abstract: Background Salmonella are able to modulate host cell functions facilitating both uptake and resistance to cellular host defence mechanisms. While interactions between bacterial modulators and cellular proteins have been the main focus of Salmonella research, relatively little is known about mammalian gene regulation in response to Salmonella infection. A major class of mammalian gene modulators consists of microRNAs. For our study we examined interactions of microRNAs and regulated mRNAs in mammalian intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 62 publications
(93 reference statements)
0
51
0
Order By: Relevance
“…87 The same authors pointed to miR-29b as a ‘female-predominant’ miRNA. Another group of miR-29 targets includes genes involved in metabolism and metabolic disorders, specifically those involved in glucose transport, 88 such as the transmembrane protein insulin-induced gene 1, 43 CAV2 , 89 monocarboxylate transporter 1 ( SLC16A1 , also known as MCT1 ), 90 and PIK3R1 , 91 which further confirm its critical role in diabetes mellitus.…”
Section: Mir-29 and The Diabetic Heartmentioning
confidence: 81%
“…87 The same authors pointed to miR-29b as a ‘female-predominant’ miRNA. Another group of miR-29 targets includes genes involved in metabolism and metabolic disorders, specifically those involved in glucose transport, 88 such as the transmembrane protein insulin-induced gene 1, 43 CAV2 , 89 monocarboxylate transporter 1 ( SLC16A1 , also known as MCT1 ), 90 and PIK3R1 , 91 which further confirm its critical role in diabetes mellitus.…”
Section: Mir-29 and The Diabetic Heartmentioning
confidence: 81%
“…Furthermore, loss of function by antagonizing miR‐103/107 levels leads to the up‐regulation of caveolin‐1, which in turn stabilizes the insulin receptor and enhanced insulin signalling. In an independent study, Hoeke et al . observed that miR‐29a regulates cellular uptake of pathogens during intestinal salmonella infection by way of caveolin‐2‐mediated targeting of focal adhesion and the actin cytoskeleton pathway.…”
Section: Micrornas As Modulators Of Lipid Rafts In Human Diseasesmentioning
confidence: 99%
“…Intracellular bacterial pathogens have been shown to interfere with expression of small non-coding, regulatory RNAs like microRNAs (miRNA) affecting host cell response signaling pathways such as apoptosis and autophagy (Rodriguez et al, 2007; Schulte et al, 2011; Sharbati et al, 2011, 2012; Hoeke et al, 2013; Pawar et al, 2016b; zur Bruegge et al, 2016). While the role of miRNAs in bacterial infections has been extensively studied and excellently reviewed in previous years (Eulalio et al, 2012; Das et al, 2016; Kim et al, 2017), we are beginning to realize the pivotal role of another class of regulatory RNA molecules, which are collectively referred to as long non-coding RNAs (lncRNAs).…”
Section: Introductionmentioning
confidence: 99%